Muscle strength and golf performance: A critical review - Torres-Ronda, L.; Sanchez-Medina, L.; Gonzalez-Badillo, J. J. (Journal of Sports Science & Medicine, 2011)
Golf has become an increasingly popular sport and a growing body of research trying to identify its main physical requirements is being published. The aim of this review was twofold: first, to examine the existing scientific literature regarding strength training and golf in healthy, non-injured, subjects; and second, to reach conclusions that could provide information on how to design more effective strength training programs to improve golf performance as well as directions for future research. Studies which analyzed the relationship between muscle strength, swing performance variables (club head speed, driving distance, ball speed) and skill (handicap, score) were reviewed. Changes in swing performance following different strength training programs were also investigated. Finally, a critical analysis about the methodologies used was carried out. The results of the reviewed studies seem to indicate that: 1) a positive relationship exists between handicap and swing performance (even though few studies have investigated this issue); 2) there is a positive correlation between skill (handicap and/or score) and muscle strength; and 3) there is a relationship between driving distance, swing speed, ball speed and muscle strength. Results suggest that training leg-hip and trunk power as well as grip strength is especially relevant for golf performance improvement. Studies that analyzed variations in swing performance following resistance-only training programs are scarce, thus it is difficult to prove whether the observed improvements are attributable to changes in strength levels. Many of the studies reviewed presented some methodological errors in their design and not all strength assessment protocols seemed appropriate. Further studies should determine muscle strength needs in relation to final swing performance, using well designed experiments and strict isoinertial assessment protocols which adequately relate to specific golf motion, age and skill level. More studies with elite participants, either professional or amateur, would be especially desirable.